KEDUDUKAN HARTA BENDA DALAM PERKAWINAN MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 - Esther Masri; Otih Handayani (Abdi Bhara, 2022)
However, these assets can cause conflicts in thehousehold because husband and wife do not understand theposition of property in marriage in the event of divorce anddeath. The position of property is regulated in Law Number 1 of1974 concerning Marriage which recognizes 3 (three) kinds ofassets, namely joint property, inherited property and acquiredproperty. Joint property is property acquired during marriage,while inheritance and acquisition are the innate property of eachhusband and wife. The property obtained by husband and wife asa gift or inheritance is under the control of each as long as theparties do not specify otherwise. The existence of legal provisionsregarding inherited and acquired assets but can be used as jointproperty by making a marriage agreement. The communityservice team at the Faculty of Law, Bhayangkara Universitycarried out legal counseling activities at the Citra VillaMangunjaya Housing, Tambun Selatan District, Bekasi regencywhich directly interacted with the community, especially thewomen in Rukun Warga 028. The purpose of this activity was toincrease public knowledge and understanding regardingownership and position of property. property in marriage, candistinguish joint property and innate property so that they knowthe rights and obligations of each towards their property. Theresults of the activities are made and documented in the form ofimplementation reports and published in scientific journals inorder to provide benefits in the academic field and at thepractical level.